2012
DOI: 10.1136/annrheumdis-2012-201611
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous abatacept on synovitis, osteitis and structural damage in patients with rheumatoid arthritis and an inadequate response to methotrexate: the ASSET randomised controlled trial

Abstract: ObjectivesThis randomised, double-blind, placebo-controlled phase IIIb study evaluated the impact of abatacept on MRI pathology as a primary outcome in methotrexate (MTX)-refractory patients with rheumatoid arthritis.MethodsPatients received intravenous abatacept (∼10 mg/kg) or placebo, on background MTX, for 4 months, followed by an 8-month open-label extension (OLE; all patients received abatacept plus MTX). Patients had 1.5T MRI with intravenous contrast at baseline, Months 4 and 12; wrist synovitis (three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
1
33
0
4
Order By: Relevance
“…The ACT-RAY MRI substudy reported early improvement of synovitis of RA patients after initiation of treatment with TCZ (17). The ASSET trial evaluated the clinical efficacy and safety of ABT as well the effect of treatment on MR imagings (18). To our knowledge, the present study is the first to compare MRI findings in RA patients treated with these three biologics.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The ACT-RAY MRI substudy reported early improvement of synovitis of RA patients after initiation of treatment with TCZ (17). The ASSET trial evaluated the clinical efficacy and safety of ABT as well the effect of treatment on MR imagings (18). To our knowledge, the present study is the first to compare MRI findings in RA patients treated with these three biologics.…”
Section: Discussionmentioning
confidence: 88%
“…In the ACT-RAY MRI substudy, Conaghan et al (17) reported significant improvement in MRI-detected synovitis after 2 weeks of treatment. The ASSET clinical trial evaluated the effects of ABT on various MRI findings, such as synovitis, BME and bone erosion (18). The present retrospective study compared the MRI findings in RA patients treated with the biologic DMARDs; IFX, TCZ and ABT during 52 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Эффективность и безопасность абатацепта исследо-вали в рандомизированных двойных слепых плацебо-контролируемых исследованиях у пациентов в возрасте старше 18 лет с активным ревматоидным артритом, рефрактерных к одному из иммунодепрессантов и/или ингибитору фактора некроза опухоли (ФНО) ␣ [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Особый интерес представляет рандомизированное двойное слепое плацебоконтролируемое исследование эффективности и безопасности абатацепта, в которое были включены 190 детей в возрасте от 6 до 17 лет с различными вариантами ЮИА (олиго-, полиартрит РФ-и РФ+, системный вариант без системных проявлений) [34].…”
Section: Introductionunclassified
“…Erosions, bone edema, and synovitis depicted by MRI have been shown to cover all aspects of truth 12,13,14,15,16,17 , and the RA MRI score (RAMRIS) for erosions, bone edema, and synovitis has also demonstrated responsiveness and discrimination 18,19,20,21,22 . Although feasibility issues such as accessibility, time, cost, and patient compliance may cause limitations in clinical practice, MRI is acceptable for clinical trials.…”
Section: Imaging and Soluble Biomarkers In Ramentioning
confidence: 99%